Effectiveness of projected visual aids in teaching a nutrition unit - Endly, Virginia Lee, author; Williamson, Maude, advisor; Heilig, Herb, committee member; Burnham, Helen, committee member; Drollinger, Pauline H., committee member; McClelland, James N., committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Nutrition -- Study and teaching; Visual education